Kazakhstan Economic Update, Summer 2021 : Turning the Tide on the COVID-19 Crisis - World Bank (World Bank, Washington, DC, 2021)
Kazakhstan’s economy started to recover in the second half of 2020, although real GDP is still lower than pre-COVID-19. After suffering the worst contraction in the past two decades, Kazakhstan’s real GDP rebounded in the third quarter of 2020, and growth has extended to the first quarter of 2021. Real GDP in Q1 2021 grew moderately at 1.9 percent in seasonally adjusted terms relative to the Q4 last year. The external environment has generally improved and lifted the value of Kazakhstan’s exports by about 5.8 percent in Q1 2021 compared with Q4 2020 in seasonally adjusted terms. In Q1 2021, China experienced a faster-than-expected economic rebound, while the euro area suffered another dip due to the COVID-19 resurgence. This update features findings on factors affecting the slow productivity growth among Kazakh firms, one of the critical development challenges. Productivity matters to sustain long-term growth and improve the standard of living. Findings from firm-level data analysis suggest a muted contribution of firms’ upgrading capability (innovation, managerial), poor allocative efficiency, and limited contribution from entry and exit dynamics. The authorities should consider coordinating policies to improve productivity growth by ensuring competition in the product market, reducing barriers for firms to entry in sectors dominated by state-owned enterprises, improving the effectiveness of investment policy and promotion, and boosting firms’ capability to innovate. Also, revisiting distortive support programs for firms should be reconsidered to avoid perpetuating inefficiencies in firms.